Improving the Competence of Arts and Culture Teachers Through a Workshop on Creating Traditional House Media Based on Pop-Up and Augmented Reality - Ambarwati, Dwi Retno Sri; Arif, Novida Nur Miftakhul; Triawan, Denny Wahyu; Firmansyah, Robby; Yuliana, Tri (Jurnal Abdimas, 2025)
This community service program aims to improve the competency of high school and vocational high school arts and culture teachers in Tasikmalaya Regency and City in developing creative, culture-based learning media. This program was motivated by the declining understanding of students about traditional Indonesian architecture due to the lack of engaging and interactive learning media. The activity was carried out through a hybrid workshop method that combined online and offline sessions. A total of 30 participants from various schools participated in the training focused on creating Pop-Up and Augmented Reality (AR) media to visualize traditional Indonesian houses in arts and culture learning. Data were collected through pre- and post-training questionnaires, observations, and interviews, then analyzed descriptively to measure the increase in participant competency. The results showed that 85% of participants experienced an increased understanding of the concept of Pop-Up and AR media, 90% were able to create Pop-Up media independently, and 95% assessed the workshop material as relevant to their learning needs. The integration of Pop-Up and AR media has proven effective in combining manual creativity and digital literacy, creating more interactive, contextual, and technology-integrated learning. This program demonstrates that collaboration between universities and MGMP can produce sustainable cultural learning innovations. It is recommended that similar training be developed in other regions to strengthen teachers' cultural literacy and digital competencies.